2010
DOI: 10.1002/rcm.4813
|View full text |Cite
|
Sign up to set email alerts
|

Concentration effects on laser‐based δ18O and δ2H measurements and implications for the calibration of vapour measurements with liquid standards

Abstract: Recently available isotope ratio infrared spectroscopy can directly measure the isotopic composition of atmospheric water vapour (δ(18) O, δ(2) H), overcoming one of the main limitations of isotope ratio mass spectrometry (IRMS) methods. Calibrating these gas-phase instruments requires the vapourisation of liquid standards since primary standards in principle are liquids. Here we test the viability of calibrating a wavelength-scanned cavity ring-down spectroscopy (CRDS) instrument with vapourised liquid standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
139
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(148 citation statements)
references
References 22 publications
7
139
2
Order By: Relevance
“…This uncertainty of the water vapour mixing ratio correction propagates into the isotope measurement uncertainty. Similar dependencies were found by Schmidt et al (2010) for the L1102-i version of the water vapour isotope instrument by Picarro. Since the correction can be different for every instrument, this characterisation step has to be done individually for every instrument.…”
Section: Dependency Of the Isotope Measurement Accuracy On Water Vaposupporting
confidence: 79%
See 1 more Smart Citation
“…This uncertainty of the water vapour mixing ratio correction propagates into the isotope measurement uncertainty. Similar dependencies were found by Schmidt et al (2010) for the L1102-i version of the water vapour isotope instrument by Picarro. Since the correction can be different for every instrument, this characterisation step has to be done individually for every instrument.…”
Section: Dependency Of the Isotope Measurement Accuracy On Water Vaposupporting
confidence: 79%
“…Many recent studies indicate similar performance of laser and conventional IRMS systems in terms of precision (Kerstel et al, 2006;Gupta et al, 2009;Sturm and Knohl, 2010). Equally relevant for atmospheric field applications, however, is the overall measurement uncertainty resulting from a range of factors like calibration, sensitivity to variations in water concentration, and retention effects from the tubing (Brand et al, 2009;Schmidt et al, 2010;Johnson et al, 2011;Rambo et al, 2011). Thus, a detailed assessment of the novel laser instruments and testing of their performance in field conditions is necessary to fully characterise the measurement uncertainty and to correct for biasing effects.…”
Section: F Aemisegger Et Al: Characterisation Of Water Vapour Isotomentioning
confidence: 99%
“…A LEAP Technologies PAL (Prep and Load) autosampler was used to inject each standard by syringe into a Picarro vaporization module, which flash evaporated the liquid injection before delivery to the Picarro instrument. Although Schmidt et al [2010] found some difference in the way Picarro vapor isotopic analyzers measure δD when the sample is liquid versus vapor, no significant difference was found in δ 18 O. To reduce cross-contamination between standards, each standard was injected 15 times and isotope ratios from the last four injections were averaged to determine the final measurement.…”
Section: Isotopic Calibrationsmentioning
confidence: 99%
“…To reduce cross-contamination between standards, each standard was injected 15 times and isotope ratios from the last four injections were averaged to determine the final measurement. A known concentration bias in the Picarro vapor isotopic analyzers causes the instrument to measure isotope ratios differently at both very low and very high humidity [Schmidt et al, 2010;Tremoy et al, 2011;Aemisegger et al, 2012]. To account for this, the five waters were sampled at up to seven mixing ratios (approximately 0.3, 0.6, 1.2, 2.4, 3.3, 6.5, and 11.9 g/kg) that were generated by controlling the amount of liquid injected into the vaporizer.…”
Section: Isotopic Calibrationsmentioning
confidence: 99%
See 1 more Smart Citation